Exploring Students’ difficulties in Understanding English Instructions in the Classroom at SMP Negeri 8 Pematangsiantar - Isabel Selmiola; Selviana Napitupulu (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Understanding English instructions is an essential part of classroom communication because it helps students follow learning activities effectively. However, many ninth-grade students still face difficulties in comprehending English instructions given by their teachers. This gap between the teacher’s intention and students’ understanding often leads to confusion and misbehavior in the classroom. Therefore, this study aims to explore the difficulties faced by ninth-grade students in understanding English instructions in the classroom at SMP Negeri 8 Pematangsiantar. This research used a descriptive qualitative method. The participants consisted of 30 ninth-grade students selected purposively. The data were collected through observation, questionnaires, and interviews. The results showed that students experienced several types of difficulties: limited vocabulary, unfamiliar pronunciation, lack of listening focus, and dependence on translation into Bahasa Indonesia. The findings also revealed that both internal and external factors influence students’ understanding. It can be concluded that teachers should use simpler language, slower speech, and visual aids to help students comprehend English instructions better.